Diagnostic tests for hepatitis C: Recent trends in electrochemical immunosensor and genosensor analysis - Uliana, Carolina V.; Riccardi, Carla S. [UNESP]; Yamanaka, Hideko [UNESP] (Baishideng Publishing Group Inc, 2014)
Hepatitis C is a liver disease that is transmitted through contact with the blood of an infected person. An estimated 150 million individuals worldwide have been chronically infected with the hepatitis C virus (hcv). Hepatitis C shows significant genetic variation in the global population, due to the high rate of viral RNA mutation. There are six variants of the virus (HCV genotypes 1, 2, 3, 4, 5, and 6), with 15 recorded subtypes that vary in prevalence across different regions of the world. A variety of devices are used to diagnose hepatitis C, including HCV antibody test, HCV viral load test, HCV genotype test and liver biopsy. Rapid, inexpensive, sensitive, and robust analytical devices are therefore essential for effective diagnosis and monitoring of disease treatment. This review provides an overview of current electrochemical immunosensor and genosensor technologies employed in HCV detection. There are a limited number of publications showing electrochemical biosensors being used for the detection of hcv. Due to their simplicity, specificity, and reliability, electrochemical biosensor devices have potential clinical applications in several viral infections. (C) 2014 Baishideng Publishing Group Inc. All rights reserved.
Keywords: Hepatitis C virus; Immunosensors; Genosensors; Electrochemical detection; Diagnostic tests